Analisis Kesiapan Kerja Lulusan Sekolah Menengah Kejuruan Jurusan Teknik Instalasi Tenaga Listrik - Siti Aisah; Oriza Candra (Jurnal Pendidikan Teknik Elektro, 2023)
This research describes the job readiness of the Electrical Power Installation Engineering Department graduates of Sekolah Menengah Kejuruan (SMK) Negeri 1 Padang. Work readiness is a person's overall condition, including physical, mental, and life experiences, as well as the willingness and ability to carry out work or an activity. The research method used in this research is a descriptive research method with a quantitative approach. The variable studied was the work readiness of graduates majoring in Electrical Power Installation Engineering at SMK Negeri 1 Padang. The research instrument used in this research is a questionnaire distributed to respondents online using a Google form with 1 variable and 6 indicators. This research questionnaire was conducted on graduates of the 2022/2023 academic year in Electrical Power Installation Engineering, totaling 30 respondents and the results obtained were 20 respondents with good work readiness results. The research results can conclude that the work readiness of graduates for the 2022/2023 academic year majoring in Electrical Power Installation Engineering at SMK Negeri 1 Padang is in a good category.